Association Between Early Trauma and Ideal Cardiovascular Health Among Black Americans: Results From the Morehouse-Emory Cardiovascular (MECA) Center for Health Equity. Issue 9 (8th September 2021) - Islam, Shabatun J.; Hwan Kim, Jeong; Joseph, Emma; Topel, Matthew; Baltrus, Peter; Liu, Chang; Ko, Yi-An; Almuwaqqat, Zakaria; Mujahid, Mahasin S.; Sims, Mario; Mubasher, Mohamed; Ejaz, Kiran; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Early trauma (general, emotional, physical, and sexual abuse before age 18 years) has been associated with both cardiovascular disease risk and lifestyle-related risk factors for cardiovascular disease, including smoking, obesity, and physical inactivity. Despite higher prevalence, the association between early trauma and cardiovascular health (CVH) has been understudied in Black Americans, especially those from low-income backgrounds, who may be doubly vulnerable. Therefore, we investigated the association between early trauma and CVH, particularly among low-income Black Americans. Methods: We recruited 457 Black adults (age 53±10, 38% male) without known cardiovascular disease from the Atlanta, GA, metropolitan area using personalized, community-based recruitment methods. The Early Trauma Inventory was administered to assess overall early traumatic life experiences which include physical, sexual, emotional abuse, and general trauma. Our primary outcome was the American Heart Association Life's Simple 7, which is a set of 7 CVH metrics, including 4 lifestyle-related factors (smoking, body mass index, physical activity, and diet) and three physiologically measured health factors (blood pressure, total blood cholesterol, and blood glucose). We used linear regression models adjusting for age, sex, socioeconomic status, and depression to test the association between early trauma and CVH and tested the early trauma by household income (<$50 000) interaction. Results: Higher levels of early trauma were associated with lower Life's Simple 7 scores (β, −0.05 [95% CI, −0.09 to −0.01], P =0.02, per 1 unit increase in the Early Trauma Inventory score) among lower, but not higher, income Black participants ( P value for interaction=0.04). Subtypes of early trauma linked to Life's Simple 7 were general trauma, emotional abuse, and sexual abuse. Exploratory analyses demonstrated that early trauma was only associated with the body mass index and smoking components of Life's Simple 7. Conclusions: Early trauma, including general trauma, emotional abuse, and sexual abuse, may be associated with worse CVH among low-, but not higher-income Black adults.